Сенсоры на основе CdZnTe для измерений рентгеновского излучения - Rybka, A. V.; Zakharchenko, A. А.; Davydov, L. N.; Shlyakhov, I. N.; Blinkin, A. A.; Kutnyi, K. V. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
Sensors based on the wide-bandgap semiconductor compound CdZnTe have been investigated. The advantages of such sensors are demonstrated: a wide range of photon flux and energy measurement, high detection efficiency, and satisfactory energy resolution without the need for deep cooling. Devices based on CdZnTe sensors are described, including a dosimeter for dose-rate monitoring and an X-ray spectrometer. The developed detection modules reliably register X-ray radiation starting from energies of 5 keV.